Avoiding Beach's Boojum Effect: Enhancing bench to bedside translation with field to laboratory considerations in optimal animal models. (September 2019) - Lambert, Kelly; Kent, Molly; Vavra, Dylan
Abstract: Pioneering comparative neuroendocrinologist Frank Beach cautioned researchers of the dangers of investing too much research energy in a single species (i.e., the laboratory rat) in the pursuit of limited behavioral investigations (e.g., learning) in his 1950 article entitled The snark was a boojum . Over a half-century later, behavioral neuroscientists continue to focus disproportionately on rodent models and, although exciting cutting-edge neuroscience techniques are currently utilized, the sophistication of behavioral approaches often lag behind these neurobiological methodological tools. The predictable, sterile laboratory environments, referred to as niceties by Beach, also present challenges to the investigation of relevant, species-specific responses to unpredictable natural environments. As more attention is directed to these methodological issues, fundamental information about nervous systems, as well as the translational value of studies utilizing various animal models, will be enhanced.